Fundamentals of Financial Management / 4th Edition - Van Horne James C (Prentice Hall, 1980)
Preface, Introduction, The Role of Financial Management, The Legal and Tax Environment, Principles of Financial Returns, The Role of Financial Markets for the Business Firm, Compound Interest and Present Value, Foundations for Valuation, Tools of Financial Analysis and Planning, Financial Analysis, Funds Analysis and Financial Planning, Working - Capital Management, Current Asset and Liability Structure Decisions, Cash and Marketable Securities, Accounts Receivable, Inventory Management and Control, Spontaneous Financing, Short-Term Borrowings, Investing in Capital Assets, Capital Budgeting, Risk and Capital Budgeting, Required Returns on Capital Investments, Capital Structure and Dividend Policies, Leveraging the Firm, Conceptual Aspects of Capital Structure, Dividend Policy and Retained Earnings, Longer-Term Financing-Instruments and Markets, Financing the Firm Externally, Term and Lease Financing, Long-Term Debt, Preferred Stock and Common Stock, Expansion and Contraction, Index.
Preface, Introduction, The Role of Financial Management, The Legal and Tax Environment, Principles of Financial Returns, The Role of Financial Markets for the Business Firm, Compound Interest and Present Value, Foundations for Valuation, Tools of Financial Analysis and Planning, Financial Analysis, Funds Analysis and Financial Planning, Working - Capital Management, Current Asset and Liability Structure Decisions, Cash and Marketable Securities, Accounts Receivable, Inventory Management and Control, Spontaneous Financing, Short-Term Borrowings, Investing in Capital Assets, Capital Budgeting, Risk and Capital Budgeting, Required Returns on Capital Investments, Capital Structure and Dividend Policies, Leveraging the Firm, Conceptual Aspects of Capital Structure, Dividend Policy and Retained Earnings, Longer-Term Financing-Instruments and Markets, Financing the Firm Externally, Term and Lease Financing, Long-Term Debt, Preferred Stock and Common Stock, Expansion and Contraction, Index.